Coronavirus Tourism: Charming voyagers in time of novel coronavirus - Dwi Pratiwi Wulandari, Mustika Syarifuddin, Wina Asty, Yayuk Puji Rahayu, Winda Yulia (International Journal of Advanced Science and Technology, 2020)
Indonesia isn’t the main nation on the planet whose travel industry and exchange are influenced by the COVID-19 flare-up, and since specialists don’t know it about the most recent infection, we can’t continue bragging about having "zero cases" up until this point. There have been affirmed cases among people who had no contact or past movement to places where there were diseases. So during circumstances such as the present, is it even insightful for the legislature (and different governments) to urge individuals to venture to the far corners of the planet for the sake of sparing income and benefits from the travel industry? Isn’t it excessively dangerous? Can the legislature or the travel industry authority ensure that vacationers won’t come down with the infection? Additionally, is it even shrewd to spend state cash on remote influencers to charm guests?